Construction and validation of a Questionnaire about heart failure patients' knowledge of their disease Construção e validação do Questionário de conhecimentos para pacientes com insuficiência - Bonin C.D.B.* (2014)
Background: The lack of tools to measure heart failure patients' knowledge about their syndrome when participating in rehabilitation programs demonstrates the need for specific recommendations regarding the amount or content of information required. Objectives: To develop and validate a questionnaire to assess heart failure patients' knowledge about their syndrome when participating in cardiac rehabilitation programs. Methods: The tool was developed based on the Coronary Artery Disease Education Questionnaire and applied to 96 patients with heart failure, with a mean age of 60.22 ± 11.6 years, 64% being men. Reproducibility was obtained via the intraclass correlation coefficient, using the test-retest method. Internal consistency was assessed by use of Cronbach's alpha, and construct validity, by use of exploratory factor analysis. Results: The final version of the tool had 19 questions arranged in ten areas of importance for patient education. The proposed questionnaire had a clarity index of 8.94 ± 0.83. The intraclass correlation coefficient was 0.856, and Cronbach's alpha, 0.749. Factor analysis revealed five factors associated with the knowledge areas. Comparing the final scores with the characteristics of the population evidenced that low educational level and low income are significantly associated with low levels of knowledge. Conclusion: The instrument has satisfactory clarity and validity indices, and can be used to assess the heart failure patients' knowledge about their syndrome when participating in cardiac rehabilitation programs.